Ingestion rate and egg production of copepods collected in the upper 20m in the eastern Mediterranean Sea in Oktober 2008 - Soultana Zervoudaki; Epaminondas Christou (PANGAEA, 2015)
This dataset based on samples taken during October 2008 in Dardanelles Straits, Marmara Sea and Bosporus Straits at the third priority stations. Copepods for the experiments were obtained with slow non-quantitative tows from the upper 50 m layer of the water column using 200 μm mesh size nets fitted with a large non-filtering cod end. For the grazing experiments we used the following copepod species: Oithona spp., Clausocalanus furcatus, Acartia clausi and Oncaea spp. and in one cladoceran species Penilia avirostris according to the relevant reference (Bamstedt et al. 2000). Copepod clearance rates on ciliates were calculated according to Frost equations (Frost 1972). Ingestion rates were calculated by multiplying clearance rates by the initial standing stocks (Bamstedt et al. 2000). Egg production rates of the dominant calanoid copepods were determined by incubation of fertilised females (eggs/female/day) collected in the 0-20m layer. Copepod egg production was measured for the copepods Clausocalanus furcatus, Paracalanus parvus,Acaria clausi. On board experiments for the estimation of copepod egg production were taken place. For the estimation of copepod production (mg/m**2/day), lengths (copepods and eggs) were converted to body carbon (Hopcroft et al., 1998) and production was estimated from biomass and weight-specific egg production rates, by assuming that those rates are representative for juvenile specific growth rates (Berggreen et al., 1988).